ダイ48ジ ニホン ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 2007 - 中村, 辰男; ナカムラ, タツオ; 野村, 幸弘; ノムラ, ユキヒロ; 島村, 哲也; シマムラ, テツヤ; 岩坪, 昇平; イワツボ, ショウヘイ; 松澤, 一雅; マツザワ, カズマサ; Nakamura, Tatsuo; Nomura, Yukihiro; et al. (2012)
P(論文) この報告は第48 次南極地域観測隊気象部門が,2007 年2 月1 日～2008年1 月31 日まで昭和基地において行った気象観測結果をまとめたものである.観測方法・測器・統計方法などは第47 次隊とほぼ同様である. 越冬期間中,特記される気象現象として次のものが挙げられる. 1) 10 月はブリザードが6 回襲来し,ブリザード日数は15 日を記録した.月平均気温は-10.8℃を記録し,これまでの高い方の極値を更新した(2006 年までの記録は1996 年10 月の-10.9℃). 2) 11 月は好天が続き,日照時間474.8 時間はこれまでの多い方の記録を更新し(2006 年までの記録は2006 年11 月の460.7 時間),6 日には日最小湿度21% を記録して極値を更新した(2006 年までの記録は1993 年11 月16 日の21%). 3)昭和基地上空のオゾン全量は,7 月の月平均オゾン全量が233 m atm-cm で最小値を更新した.また,8 月中旬から10 月下旬までオゾンホールの目安となる220 m atm-cm をほぼ継続的に下回った.2007 年の最小値は,10 月5 日の138 matm-cm であった(2006 年までの最小値は2006 年10 月17 日の114 m atm-cm). This report describes the results of meteorological observations at Syowa Station from February 1st, 2007 to January 31st, 2008, carried out by the Meteorological Observation Team of the 48th Japanese Antarctic Research Expedition(JARE-48). The observation methods, instruments and statistical methods used by JARE-48 were almost the same as those used by the JARE-47 observation team. Remarkable weather phenomena observed during the period of JARE-48 are as follows.1) In October 2007, there were 6 blizzards and 15 blizzard days, and the monthly mean temperature was -10.8℃, which was the highest record for Syowa Station.2) In November 2007, the monthly sunshine duration at Syowa Station was 474.8 hours, which was the longest record, and minimum humidity 21% updated minimum.3) The monthly mean amount of total ozone over Syowa Station in July was 233 m atm-cm, which was the lowest record. The amount of total ozone became lower than or equal to 220 m atm-cm from mid-August to end of October. On October 5th, the amount of total ozone was 138 m atm-cm, which was the lowest value in 2007. departmental bulletin paper